2007
DOI: 10.1097/inf.0b013e31806211bf
|View full text |Cite
|
Sign up to set email alerts
|

Orf Virus Infection in Children: Clinical Characteristics, Transmission, Diagnostic Methods, and Future Therapeutics

Abstract: Orf virus leads to self-limited, subacute cutaneous infections in children who have occupational or recreational contact with infected small ruminants. Breaches in the integument and contact with animals recently vaccinated for orf may be important risk factors in transmission. Common childhood behaviors are likely important factors in the provocation of significant contact (ie, bites) or in unusual lesion location (eg, facial lesions). Clinician recognition is important in distinguishing orf infection from li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 23 publications
1
50
0
7
Order By: Relevance
“…The mini-array assay used in our study revealed that some of the animals affected by severe proliferative lesions, clinically defined as papillomas, were in fact coinfected with zoonotic PCPV, BPSV, and OPV. It is important to emphasize that zoonotic poxviruses share risk factors and clinical features with other life-threatening diseases in humans 18 ; for this reason, rapid and reliable diagnostic methods, like the one used in our study, have the potential to allow the rapid assessment of potentially fatal infections in humans. With the aid of this new method, it was possible to demonstrate that 2 goats and 2 cows, from different farms, were coinfected with different epitheliotropic viruses.…”
mentioning
confidence: 99%
“…The mini-array assay used in our study revealed that some of the animals affected by severe proliferative lesions, clinically defined as papillomas, were in fact coinfected with zoonotic PCPV, BPSV, and OPV. It is important to emphasize that zoonotic poxviruses share risk factors and clinical features with other life-threatening diseases in humans 18 ; for this reason, rapid and reliable diagnostic methods, like the one used in our study, have the potential to allow the rapid assessment of potentially fatal infections in humans. With the aid of this new method, it was possible to demonstrate that 2 goats and 2 cows, from different farms, were coinfected with different epitheliotropic viruses.…”
mentioning
confidence: 99%
“…20 can lead to secondary bacterial infection, 5 and the author has treated several of these cases. When orf affects the pulp of the digits, it is usually mistaken for a felon, and one French report called it the faux panaris or false felon.…”
Section: Diagnosismentioning
confidence: 97%
“…Ancak tanı genellikle temas öyküsü ve karakteristik lezyonların görülmesiyle konmaktadır (3,8,9,12). Doku kültüründen virus izolasyonu primer olarak koyun veya sığır hücreleri gerektirir ve elde etmek zor olabilmektedir (3).…”
Section: İrdelemeunclassified